Stone and Village Memory: The Temporality of Cultural Landscapes Constituted by the Dolmens of Seongsong-myeon, Gochang - Noh, Younghee (International Journal of Knowledge Content Development & Technology, 2026)
This study analyzes how the dolmens of Seongsong-myeon, Gochang, intertwine with village memory to shape the temporality of a cultural landscape. We combine place, memory, and landscape perspectives and triangulate field records with terrain-horizon readings, ritual reports, and oral histories. Siting and axial orientation inscribe seasonal horizons and rhythms, while ritual, commemoration, and pedagogy translate them into social memory. We trace shifts in interpretation—from colonial surveys and development to World Heritage discourse—and their effects on place-making. Framed as “landscaping temporality,” the results inform outdoor interpretation, STEAM, sky friendly lighting, and inclusive routes, repositioning megalithic heritage from archaeological chronology toward community life.